Feasibility and Acceptability of an Internet-Based, African Dance-Modified Yoga Program for African-American Women with or at Risk for Metabolic Syndrome - Johnson, Candace C (J Yoga Phys Ther, 2014)
African-American (AA) women are the segment of the population that experiences the highest mortality from metabolic syndrome (MetS). Yoga decreases risk of MetS, yet there have been no yoga studies of AA women with or at risk for MetS. The purpose of this 4-week study was to test the feasibility and acceptability of a culturally tailored, Internet-based intervention, yogic dance (YD), using digital videos in a sample of AA women (ages 35-64) at risk for or with MetS. The investigators examined the rates of accrual, attrition, and reasons for attrition; the feasibility of using the Internet to deliver the intervention; the acceptability of the intervention as structured; and any other benefits and/or limitations of YD. The study used a single-group, mixed-methods design underpinned by social constructivist theory and Pender's Health Promotion Model. Twenty-four women provided consent to enroll in the study. After completing in-person semi-structured interviews and Internet-based measures, including the Physical Activity Readiness Questionnaire, and the modified International Physical Activity Questionnaire, consented participants engaged in 4-weeks of the yogic dance intervention via daily video-based instructions located on the study Web site. After the intervention, four women participated in focus groups to voice their perceptions of barriers to and benefits from YD and the acceptability of using the YD intervention. The investigators analyzed focus group data using content/thematic analysis and validated themes with baseline semi-structured interviews. The majority of the women (79%) found YD acceptable. Themes that emerged from the descriptive data include: (1) Culture is an important aspect of yogic dance; and (2) Increased social support would enhance yogic dance participation. The integrated results from this feasibility study will inform research exploring the complex correlates that influence health behaviors in AA women.